Enhanced glucocorticoid‐induced leucine zipper in dendritic cells induces allergen‐specific regulatory CD4+T‐cells in respiratory allergies. Issue 5 (10th March 2014) - Karaki, S.; Garcia, G.; Tcherakian, C.; Capel, F.; Tran, T.; Pallardy, M.; Humbert, M.; Emilie, D.; Godot, V.
Abstract Background Respiratory allergies rely on a defect of IL‐10‐secreting regulatory CD4+T‐cells (IL‐10‐Tregs) leading to excessive Th2‐biased immune responses to allergens. According to clinical data, the restoration of allergen‐specific IL‐10‐Tregs is required to control respiratory allergies and cure patients. The discovery of mechanisms involved in the generation of IL‐10‐Tregs will thus help to provide effective treatments. We previously demonstrated that dendritic cells (DCs) expressing high levels of the glucocorticoid‐induced leucine zipper protein (GILZ) generate antigen‐specific IL‐10‐Tregs. Objective We suspect a defective expression of GILZ in the DCs of respiratory allergic patients and speculate that increasing its expression might restore immune tolerance against allergens through the induction of IL‐10‐Tregs. Methods We assessed GILZ expression in blood DCs of patients and healthy nonallergic donors by qPCR. We compared the ability of patients' DCs to induce allergen‐specific IL‐10‐Tregs before and after an in vivo up‐regulation of GILZ expression by steroid administration, steroids being inducers of GILZ. Results We report lower levels of GILZ in DCs of respiratory allergic patients that return to normal levels after steroid administration. We show that patients' DCs with increased levels of GILZ generate allergen‐specific IL‐10‐Tregs again. We further confirm unequivocally that GILZ is required in patients' DCs to activate these IL‐10‐Tregs. Conclusion This proof of concept study shows that the re‐establishment of GILZ expression in patients' DCs to normal levels restores their capacity to activate allergen‐specific IL‐10‐Tregs. We thus highlight the up‐regulation of GILZ in DCs as a new interventional approach to restore the immune tolerance to allergens.